On the Duty of Fidelity of Husband and Wife (Asian Journal of Social Science Studies, 2022)
Nowadays, due to the change of customs and order and the adverse influence of some foreign decaying economy and culture, social phenomena such as "fall in love the other woman" that undermine the harmony of the relationship between husband and wife and damage the legitimate rights and interests of one of the spouses are becoming more and more intense. For this reason, the author believes that it is very necessary for China's new Marriage Law to establish the duty of fidelity between husband and wife. By expounding the connotation and performance of the fidelity obligation of husband and wife and giving certain suggestions, this paper reveals the significance of the fidelity obligation of husband and wife, hoping to provide an opinion for its progress and development, promote China's marriage and family law to better solve social problems, and help more couples to fulfill their fidelity obligations and enjoy warm and harmonious family relations.